Public Communication And The Complexity Of Environmental Concerns In Algeria: Acts And Strategies - Bouguettaya Nassim (جامعة الوادي - University of Eloued, 2022)
The present research work focuses on the communication dimension of public action in terms of protection and promotion of the environment in Algeria. Nonetheless, it is worth pointing out that this public communication is the responsibility of the Ministry in charge of the Environment as part of its assignment of education, awareness and partnership for the protection of the environment, and the promotion of sustainable development. In the actual research, a sample of these actions is studied in order to better understand the modes of communication used by this public institution and the resulting strategies bearing in mind that the greatest attention is to be given to children's communication (especially those in school), to event-related communication, to associative communication and to public (inter-ministerial) communication.
article
Keywords: Public Communication , Environment , Actions , Strategies